Relationship between feed management toward stress responses and welfare of horses in Malaysia - Juhari, Farah Hanis (2022)
Stabling practices significantly alter horses’ dietary and natural feeding behaviour, leading to the development of abnormal oral behaviours (AOB) such as oral stereotypy (OS) and redirected behaviour (RB). The present study has four studies. Study 1 was a cross-sectional study that were conducted in seven established equine facilities in Klang Valley, Malaysia, using 207 working horses consisted of equestrians, leisure riding, endurance, polo sport and patrolling. Data on the management and feeding practices were collected in each facility, and the horses behaviours were observed. In Study 2, a proximate analysis was conducted on feedstuffs to determine the nutritional composition and the horses’ total daily dietary intake from each working group (n = 207), and their interaction with the two types of AOB (OS and RB). In Study 3, blood samples were collected from 48 horses representing low and high AOB levels from each of the horse working groups for the determination of haematology and biochemical parameters, plasma cortisol, ghrelin, and leptin concentrations, as well as the telomere length expression. Lastly, Study 4 determined the effect of a high forage, high fiber (HFHF) and high concentrate, low fiber (HCLF) diets on patrolling horses with high and low AOB levels. Findings found the amount of hay fed greatly influenced the expression of abnormal behaviors. Whereas, horses with longer working hours were more vulnerable to OS. The blood biochemistry profile was different between high- and low AOB horses. Plasma ghrelin and leptin were exclusively influenced by AOB. Telomere length was not associated with AOB. The data were further supported by the feeding experiment with HFHF and HCLF diets, which indicated that the type of diet affects the performance of AOB through their influence on ghrelin and leptin hormones except on telemere length. Hence, the present study provides novel findings that ghrelin and leptin hormones could be used as potential stress biomarkers in horses suffering from AOB.